Study the Microbiologically Influenced Corrosion of Carbon Steel - Zuheir T.Khulief.Al-Tai (Engineering and Technology Journal, 2011)
The main objective of this study was to evaluate the microbiologically influenced corrosion of carbon steel in water, samples of water taken from Al-Hilla rivers and distill water (control medium ). Corrosion analyses by using (Liner polarization tafel test; weight loss method ; microstructure examination , surface roughness test and X-Ray diffraction analysis) and microbiological analyses by using (Isolation and identification by using appearance factors microscopic ,culturing factors and biochemical tests for biofilm of corrosion product) are used in this study. The result of corrosion analyses shows the corrosion rates of carbon steel in rivers water are more than that in control water, the microstructure examination and surface roughness tests show increase in roughness of met.al. surfaces which are under the corrosion medium (rivers water) compared with control medium. The result of microbiological analyses shows the slides that made from the biofilm (product of corrosion) under microscopic appear small bacilli negative gram strain (G-ve) bacteria, where as culturing test shows small colonies with 2.5ìm in diameter of bacteria have mucin appearance and green pigments as well as the result from biochemical tests; these facts indicate that Pseudomonas aeruginosa bacteria are correlated with the type of corrosion occurring in the carbon steel in the rivers water.